2019
DOI: 10.1111/tbj.13207
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence-guided lumpectomy of nonpalpable breast cancer versus wire-guided excision: A randomized clinical trial

Abstract: The use of wire localization (WL) for excisions of nonpalpable breast cancer (NBC) has several disadvantages. The purpose of this study was to evaluate the use of indocyanine green‐guided nonpalpable breast cancer lesion localization (INBCL) and to compare it with WL. A total of 62 patients with a preoperative histological diagnosis of NBC lesions that could be visualized with ultrasound and mammography were randomized to INBCL or WL. Patients with preoperatively diagnosed primary ductal carcinoma in situ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…In total, 24 RCTs fulfilled our inclusion criteria and were included in this systematic review and NMAs ( Fig. 1 ) [ 16 , 27 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Of the 24 RCTs included in this analysis, almost 40.0% were conducted in European surgical research institutions (37.5%, 9/24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 24 RCTs fulfilled our inclusion criteria and were included in this systematic review and NMAs ( Fig. 1 ) [ 16 , 27 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Of the 24 RCTs included in this analysis, almost 40.0% were conducted in European surgical research institutions (37.5%, 9/24).…”
Section: Resultsmentioning
confidence: 99%
“…There was low to moderate risk of bias among the included RCTs: Overall, 10 of the included RCTs had low-risk of bias (41.7%) [ 27 , 42 , 45 , 50 , 51 , 53 , 54 , 57 , 61 , 62 ], 12 of the RCTs included some concerns for bias (60.0%) [ 16 , 24 , 41 , 44 , [47] , [48] , [49] , 52 , 55 , [58] , [59] , [60] ], while 2 RCTs were considered high-risk of bias (10.0%) [ 46 , 56 ]. Risk of bias assessment is illustrated in the Supplementary Appendix 1 .O.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous case report on non-palpable breast lesion localization, ICG-F guided occult lesion localization (IFOLL) demonstrated successful surgical excision indicating that IFOLL was a clinically acceptable procedure 8 . A randomized clinical trial using ICG-F localization for non-palpable lesions showed that the rate of clear margins was significantly high (87.5% in the ICG-F group vs. 63.3% in the wire localization group, p = 0.026) 10 . Another study on the excision of non-palpable breast cancer using ICG-F confirmed localization of 100% and a safe margin at about 95% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports of excisions which injected ICG-F into the intra-tumor for non-palpable lesions of breast cancer. Localized excisions using ICG-F have been shown to be possible as an alternative to previous existing methods 8 10 . However, a study of excisions using sono-guided peritumor ICG-F injections for breast cancer has yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, both CNSL and MBL help to accomplish the complete resection of 172 lesions, indicating that the dye localization was a feasible and effective auxiliary technique in the resection of NPBL. Complete resection of NPBL while avoiding excessive resection of normal tissue is significant for cosmetic outcomes ( 32 ). Our results revealed that the TRV and CRR of the CNSL group were significantly lower compared to those of the MBL group.…”
Section: Discussionmentioning
confidence: 99%